TUGAS TENAGA PENDIDIK DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI ERA DISRUPSI TEKNOLOGI PADA SEKOLAH DASAR ISLAM TERPADU TIARA PEKANBARU - Yanti, Annisa Darma; Andriani, Tuti; Aryani, Nini; bin Jamaludin, Muhammad Arif Sufyan (Idaarah: Jurnal Manajemen Pendidikan, 2024)
In the era of technological disruption, the roles and responsibilities of educators in improving the quality of education have become increasingly complex and dynamic. Teachers are not only required to adapt to technological advancements but also to continuously develop new competencies relevant to ongoing changes. This study aims to analyze the roles of educators in enhancing the quality of education during the technological disruption era at Tiara Integrated Islamic Elementary School (SDIT) in Pekanbaru. Using a qualitative approach with field study methods, the research seeks to explore educators' tasks in utilizing technology, addressing challenges, and implementing innovative teaching strategies. Data sources were obtained from key informants, namely the principal and teachers. Data collection techniques included interviews and observations. The data analysis stages involved data collection, reduction, and interpretation. In facing the era of technological disruption, educators at Tiara SDIT Pekanbaru carry out various strategic tasks to improve the quality of education. Various strategies are also implemented to enhance educators' competencies through training and workshops on educational technology. Another strategy involves strengthening students' character through value-based education. Through these efforts, the quality of education at SDIT Tiara Pekanbaru continues to improve by effectively leveraging available technology.